Analysis of Possibility of New Generation Satellite Communications for Navigation - Štambuk, Igor; Malarić, Krešimir (Transactions on Maritime Science, 2024)
Satellite communication has become an indispensable technology for modern society, providing global connectivity and enabling a wide range of applications such as navigation, weather forecasting, and data transmission. However, the efficiency and security of satellite communication channels are still challenging issues that require continuous improvement. This article presents recent advances and the state of art in satellite communication technology. Specifically, we discuss the RF power flux density, received power and received signal power. Using the RF PROP application, we compared the link characteristics of the leading satellite service providers depending on whether they broadcast from geostationary, medium, or low Earth orbit.